Validity, reliability, and feasibility of the digital motor performance test (DigiMot) - Klein, T.; Pauli, M.; Greiner, J.; Hanssen-Doose, A. (Frontiers in Sports and Active Living, 2025)
Introduction: Assessing and monitoring physical fitness in children and adolescents requires valid, reliable, and feasible tests. The digital motor performance test (DigiMot) was developed for remote assessment via videoconference. This study evaluated its validity, reliability, and feasibility in children and adolescents.